USE OF THE PREPARATION CHLORMEQUAT CHLORIDE TO INCREASE RESISTANCE OF REGENERATED POTATO - I. ANIKINA; T. BEKSEITOV; G. DJAKSYBAEVA (International Journal of Pharma and Bio Sciences, 2015)
In world practice, of primary seed potato micropropagation actively used the original seed. Application of growth regulators can significantly improve the efficiency of the accelerated reproduction at all stages of production, in particular the use of seedling culture to reduce losses during transplantation the culture of plants in vivo. In this paper we investigate the possibility of applying retardant chlormequat chloride in the composition of the culture medium of Murashige-Skoog for increasing the adaptive properties of regenerated potato. Studies have shown that the use of the drug in the dosage chlormequat chloride 0,3 ml / l culture medium consisting of Murasige-Skuga culture stimulates adaptive properties of plants and reduce their losses during transplantation in vivo by 21%. Application of the preparation chlormequat chloride in the final stages of micropropagation can significantly improve the efficiency of the technology gain valuable biotechnological material for primary seed potatoes.